LIFESTYLE OF HEALTH WORKERS FROM PEDIATRIC UNITS DURING THE PANDEMIC: A CROSS-SECTIONAL STUDY - Milena Oliveira Coutinho; Michael Daian Pacheco Ramos; Larissa de Souza Correia; Jorge Lopes Cavalcante Neto (Journal of Physical Education)
ABSTRACT This study aimed to assess the lifestyle of health workers in pediatric units of Bahia, Brazil, by comparing the total and domain scores of the Fantastic Lifestyle Questionnaire (FLQ) according to sex, age group, and employment profile. This cross-sectional study included 407 health workers from four pediatric health units in Bahia. The FLQ and a sociodemographic questionnaire were answered via Google Forms during the COVID-19 pandemic. Men scored significantly lower than women in the ‘tobacco and toxics’ (p = 0.046) and ‘alcohol’ (p < 0.001) domains but higher in the ‘sleep, seat belt, stress, and safe sex’ domain (p = 0.01). Younger health workers (18 to 34 years old) scored significantly higher than older workers (35 to 64 years old) in the ‘tobacco and toxics’ domain (p = 0.03). Direct healthcare workers (e.g., nurses and doctors) scored significantly higher than indirect healthcare workers (e.g., administrators) in the ‘tobacco and toxics’ domain (p = 0.04). Despite the COVID-19 pandemic, the lifestyle of most workers was classified as very good (56.02%). Our findings indicate changes in the lifestyle of health workers, especially concerning the use of tobacco, alcohol, and conditions related to sleep, stress, safe sex, and traffic safety behaviors. Future studies are recommended to understand better the determinants and conditioning factors of tobacco use by health workers and design targeted public health initiatives.